A photoresist specially used for high-precision radio frequency antenna and its manufacturing method
By adding composite toughening filler and high-temperature resistant additives to the photoresist, combined with modified cellulose nanowhiskers and gelatin grafting reactions, the problem of insufficient moisture resistance and toughness of photoresist in high-temperature environments is solved, and the excellent high-temperature resistance, viscosity and toughness required for high-precision radio frequency antenna manufacturing is achieved.
Patent Information
- Application Number
- CN202411211999.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-30
AI Technical Summary
Existing photoresist is insufficient in humidity resistance and toughness in high-temperature environments, which is prone to deformation or cracks, resulting in reduced performance and scrapping, and cannot meet the manufacturing needs of high-precision radio frequency antennas.
The photoresist is used with epoxy resin and active ester curing agent as the main components, and the composite toughening filler and high-temperature resistant additive are added. Through the reaction of modified cellulose nanowhiskers and gelatin grafting, the toughness and viscosity of the photoresist are enhanced and its stability at high temperature is improved.
The high temperature resistance, viscosity and toughness of the photoresist are improved, so that it can remain undeformed at 250℃ for 28 hours, the peel strength of 180° can reach 16.2N/25mm, and the elongation of break can reach 251%, extending the service life of the photoresist.
Smart Images

Figure CN118963062B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photoresists, and in particular to a photoresist dedicated to high-precision radio frequency antennas and a manufacturing method thereof. Background Art
[0002] With the development of modern communication technology, the application and usage of RFID antennas are increasing. The technical accuracy of traditional gravure printing technology, especially in high-frequency signal processing and transmission, can no longer meet the high-precision packaging technology level. In order to solve the problem, photoresist has entered people's field of vision. Photoresist plays an important role in high-precision RF antennas, which is mainly reflected in the fine graphic processing link in the antenna manufacturing process. The precise manufacturing of high-precision RF antenna structure is achieved through the photolithography process. The accuracy of photoresist determines the manufacturing accuracy of the antenna, which is very important for improving the performance of the antenna, reducing losses and enhancing anti-interference capabilities.
[0003] Photoresist, also known as photoresist, is mainly composed of film-forming resin, photosensitizer, additives and solvent. The present invention adopts epoxy resin as the film-forming resin and utilizes active ester to cure the epoxy resin to obtain an epoxy resin cured product with excellent dielectric properties. The photoresist composed of epoxy resin and active ester curing agent solves the problem of moisture resistance to a certain extent. There is no polar hydroxyl group in the structure. At the same time, under the action of heat, the active ester cured epoxy resin can be ring-opening polymerized to obtain a cross-linked polymer. However, the cross-linking density is relatively low, the cured product is brittle and has insufficient toughness. Therefore, the photoresist using epoxy resin as the film-forming resin is difficult to take into account high temperature resistance, adhesion and toughness, and cannot meet the actual application requirements. The poor high temperature resistance will cause the photoresist to easily deform or form cracks under high temperature conditions, resulting in performance degradation and even causing the photoresist to be scrapped. The poor adhesion performance will cause the photoresist to easily fail in adhesion, resulting in deformation or falling off. The insufficient toughness will affect the performance and precision of the photoresist. The patent with publication number CN110441989B discloses a photoresist composition, which includes an organic amine and organic silicon dual modified phenolic resin, an acrylate modified epoxy resin, a methacrylic acid copolymer resin, an anti-shrinkage agent, tris (2,3-dibromopropyl) isocyanate, a photoactive agent, an adhesion promoter, an organic silicon leveling agent, an additive and a solvent. The prepared photoresist has the advantages of good adhesion and excellent corrosion resistance. However, the patent does not take into account that in actual applications, the high temperature resistance and toughness of the photoresist are poor, and it is easy to deform or crack in a high temperature environment, resulting in performance degradation and the scrapping of the photoresist, as well as the impact on the performance and precision of the photoresist. Therefore, the present invention provides a photoresist with excellent high temperature resistance, viscosity and toughness, which meets the application requirements of the photoresist in a high temperature environment and has positive practical significance. Summary of the invention
[0004] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a photoresist and a manufacturing method dedicated to high-precision radio frequency antennas.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A photoresist specially used for high-precision radio frequency antenna comprises the following raw materials in parts by weight: 60-80 parts of epoxy resin, 25-45 parts of active ester curing agent, 0.1-0.5 parts of curing accelerator, 3-5 parts of composite toughening filler, 4-6 parts of high temperature resistant additive, 3-6 parts of photoacid generator and 80-100 parts of solvent.
[0007] Furthermore, the preparation method of the composite toughening filler comprises the following steps:
[0008] Step A, adding cellulose nano whiskers to dimethyl sulfoxide, stirring and mixing evenly, introducing nitrogen protection, adding p-formylbenzoic acid and p-toluenesulfonic acid, then raising the temperature to 90-100° C., stirring and reacting for 4-6 hours, filtering, washing, and drying to obtain modified cellulose nano whiskers;
[0009] Step B, dispersing the modified cellulose nano whiskers in deionized water to form a uniform dispersion, introducing nitrogen for protection, adding gelatin, adjusting the pH, stirring and reacting at 50-60° C. for 3-6 hours, centrifugally separating, washing, and drying to obtain a composite toughening filler.
[0010] By adopting the above technical scheme, the surface of the cellulose nanowhiskers has active hydroxyl groups, which can undergo esterification reaction with the carboxyl groups in the p-formylbenzoic acid structure under the catalytic action of p-toluenesulfonic acid, thereby introducing aldehyde groups on the surface of the cellulose nanowhiskers to obtain modified cellulose nanowhiskers. The aldehyde groups in the modified cellulose nanowhiskers structure can undergo Schiff base reaction with the amino groups in the gelatin structure to obtain cellulose nanowhiskers grafted with gelatin, which is a composite toughening filler. Gelatin grafted cellulose nanowhiskers act as a bridge between the epoxy resin and the surface of cellulose nanowhiskers, effectively improving the compatibility of cellulose nanowhiskers with epoxy resin, enabling the cellulose nanowhiskers to be evenly dispersed in the epoxy resin matrix, avoiding agglomeration, and enhancing the bonding strength between cellulose nanowhiskers and epoxy resin. Cellulose nanowhiskers can better play their own advantages, absorb impact energy when impacted, bear loads, and better disperse stress, thereby enhancing the toughness of epoxy resin. The gelatin structure also contains carboxyl groups, which can make the composite toughening filler and the epoxy resin matrix entangled with each other, improve the density of the epoxy resin matrix structure, enhance viscosity, and further improve the toughness of the epoxy resin, thereby improving the toughness and viscosity of the photoresist.
[0011] Furthermore, in step B, the pH is 4.5-5.5.
[0012] Furthermore, the preparation method of the high temperature resistant additive is as follows:
[0013] Add 1,4-phenylenedi(dimethylsilanol) to dimethyl sulfoxide, introduce nitrogen protection, stir for 10-15 minutes, add ternary chloroacetic acid resin and acid binding agent, raise the temperature to 70-90°C, react for 5-8 hours, and after the reaction is completed, cool to room temperature, precipitate, filter, wash, and vacuum dry at 40-60°C to obtain a high temperature resistant additive.
[0014] By adopting the above technical scheme, the active chlorine substituent in the structure of the ternary chloroacetic acid resin is substituted with the alcoholic hydroxyl group in the structure of 1,4-phenylenedi(dimethylsilanol) to obtain a high temperature resistant additive. The structure of the high temperature resistant additive introduces a high temperature resistant rigid benzene ring and a high bond energy high temperature resistant silicon oxygen bond, which can inhibit the movement, breakage and decomposition of the molecular chain at high temperature, and improve the high temperature resistance and thermal stability of the epoxy resin. The ternary chloroacetic acid resin is sticky and can form a strong bonding force with the surface of the adhered substrate to enhance the viscosity. The high temperature resistant additive structure contains a carboxyl group, which can be entangled with the epoxy resin matrix, improve the interface bonding with the epoxy resin, and avoid the phenomenon of phase separation. At the same time, it can further improve the high temperature resistance and viscosity, and can produce a synergistic viscosity-enhancing effect with the composite toughening filler, so as to avoid deformation or cracking of the photoresist under high temperature environment, degradation of performance, and degradation of viscosity, resulting in failure of the photoresist, and prolonging the service life of the photoresist.
[0015] Furthermore, the acid binding agent is sodium carbonate or sodium bicarbonate.
[0016] Furthermore, the epoxy resin is EPON SU8; the active ester curing agent is EPI CLON HPC-8000-65T; the curing accelerator is dimethylaminoethanol; and the photoacid generator is any one of diphenyliodonium hexafluorophosphate, diphenyl p-tert-butylphenyl trifluoromethanesulfonate, and diphenyl p-isobutylphenyl trifluoromethanesulfonate.
[0017] Furthermore, the solvent is any one of ethylene glycol monomethyl ether acetate, propylene glycol methyl ether, diethylene glycol dimethyl ether, propylene glycol methyl ether acetate, diethylene glycol methyl ethyl ether, methyl ethyl ketone, isopropyl alcohol, and cyclohexanone.
[0018] A method for manufacturing a photoresist specially used for high-precision radio frequency antennas is as follows:
[0019] According to parts by weight, epoxy resin, active ester curing agent, curing accelerator, composite toughening filler, high temperature resistant additive and photoacid generator are added into the solvent, and the components are stirred and mixed evenly to obtain the photoresist.
[0020] Beneficial effects of the present invention:
[0021] The photoresist prepared by the present invention is added with a composite toughening filler and a high-temperature resistant additive. The prepared photoresist can remain unchanged for 28 hours at 250°C, has a 180° peel strength of up to 16.2N / 25mm, and an elongation at break of up to 251%. It has excellent high-temperature resistance, viscosity and toughness, can maintain stable performance in a high-temperature environment, is not easy to be damaged, and is not easy to fall off, so that the photoresist has a long service life and broad application prospects.
[0022] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0024] Figure 1 2 are scanning electron microscope images of the cellulose nano whiskers and the composite toughening filler in the present invention at a magnification of 2000 times, wherein A is a scanning electron microscope image of the cellulose nano whiskers at a magnification of 2000 times, and B is a scanning electron microscope image of the composite toughening filler at a magnification of 2000 times;
[0025] Figure 2 It is the infrared spectrum of the high temperature resistant additive in the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The preparation methods of the composite toughening filler and the high temperature resistant additive used in the following examples and comparative examples of the present invention are as follows:
[0028] 1. Preparation of composite toughening filler
[0029] Step A, adding 2.5 g of cellulose nano whiskers to dimethyl sulfoxide, stirring and mixing, introducing nitrogen protection, adding 1.8 g of p-formylbenzoic acid and 0.3 g of p-toluenesulfonic acid, then raising the temperature to 95° C., stirring and reacting for 5 h, filtering, washing, and drying to obtain modified cellulose nano whiskers;
[0030] Step B: Disperse 2.3 g of modified cellulose nano whiskers in deionized water to form a uniform dispersion, introduce nitrogen protection, add 2 g of gelatin, adjust the pH to 5, stir and react at 52° C. for 6 h, centrifuge, wash and dry to obtain a composite toughening filler.
[0031] The cellulose nano whiskers and composite toughening fillers were analyzed by scanning electron microscope using KYKY-2800B. The test results are as follows: Figure 1 As shown, A is a scanning electron microscope image of cellulose nano whiskers at a magnification of 2000 times, and B is a scanning electron microscope image of the composite toughening filler at a magnification of 2000 times. Figure 1 It can be seen that the surface of cellulose nanowhiskers is smooth, while the surface of the composite toughening filler is rough. The rough surface of the composite toughening filler is caused by the reaction between gelatin and modified cellulose nanowhiskers.
[0032] 2. Preparation of high temperature resistant additives
[0033] 1.5 g of 1,4-phenylenedi(dimethylsilanol) was added to dimethyl sulfoxide, nitrogen was introduced for protection, and after stirring for 10 min, 2.8 g of ternary chloroacetic acid resin and 0.4 g of sodium bicarbonate were added, and the temperature was raised to 80°C and reacted for 6 h. After the reaction was completed, the mixture was cooled to room temperature, precipitated, filtered, washed, and vacuum dried at 50°C to obtain a high temperature resistant additive.
[0034] The potassium bromide tablet method was used to prepare the sample, and the high temperature resistant additives were tested by infrared spectrometer, such as Figure 2 As shown in the figure, analysis shows that in the infrared spectrum of the high temperature resistant additive, 3060cm -1 The absorption peak of the carbon-hydrogen bond on the benzene ring appeared at 1735 cm -1 The absorption peak of carbonyl carbon-oxygen double bond appeared at 1019 cm -1 The absorption peak of silicon-oxygen bond appeared at 776 cm -1 The absorption peak of silicon-carbon bond appears at
[0035] Example 1
[0036] Photoresist manufacturing
[0037] 60 g of epoxy resin EPON SU8, 25 g of active ester curing agent EPICLON HPC-800-65T, 0.1 g of dimethylaminoethanol, 3 g of composite toughening filler, 4 g of high temperature resistant additive, and 3 g of diphenyliodonium hexafluorophosphate were added to 85 g of diethylene glycol methyl ethyl ether, and the components were stirred and mixed to obtain a photoresist.
[0038] Example 2
[0039] Photoresist manufacturing
[0040] 65 g of epoxy resin EPON SU8, 30 g of active ester curing agent EPICLON HPC-800-65T, 0.3 g of dimethylaminoethanol, 4 g of composite toughening filler, 5 g of high temperature resistant additive, and 4 g of diphenyliodonium hexafluorophosphate were added to 90 g of diethylene glycol methyl ethyl ether, and the components were stirred and mixed to obtain a photoresist.
[0041] Example 3
[0042] Photoresist manufacturing
[0043] 70 g of epoxy resin EPON SU8, 40 g of active ester curing agent EPI CLON HPC-800-65T, 0.4 g of dimethylaminoethanol, 4.5 g of composite toughening filler, 5.5 g of high temperature resistant additive, and 5 g of diphenyl iodonium hexafluorophosphate were added to 95 g of diethylene glycol methyl ethyl ether, and the components were stirred and mixed to obtain a photoresist.
[0044] Example 4
[0045] Photoresist manufacturing
[0046] 80 g of epoxy resin EPON SU8, 45 g of active ester curing agent EPI CLON HPC-800-65T, 0.5 g of dimethylaminoethanol, 5 g of composite toughening filler, 6 g of high temperature resistant additive, and 6 g of diphenyl iodonium hexafluorophosphate were added to 100 g of diethylene glycol methyl ethyl ether, and the components were stirred and mixed to obtain a photoresist.
[0047] Comparative Example 1
[0048] Photoresist manufacturing
[0049] 65 g of epoxy resin EPON SU8, 30 g of active ester curing agent EPI CLON HPC-800-65T, 0.3 g of dimethylaminoethanol, 4 g of composite toughening filler, and 4 g of diphenyliodonium hexafluorophosphate were added to 90 g of diethylene glycol methyl ethyl ether, and the components were stirred and mixed to obtain a photoresist.
[0050] Comparative Example 2
[0051] Photoresist manufacturing
[0052] 65 g of epoxy resin EPON SU8, 30 g of active ester curing agent EPI CLON HPC-800-65T, 0.3 g of dimethylaminoethanol, 5 g of high temperature resistant additive, and 4 g of diphenyliodonium hexafluorophosphate were added to 90 g of diethylene glycol methyl ethyl ether, and the components were stirred and mixed to obtain a photoresist.
[0053] Comparative Example 3
[0054] Photoresist manufacturing
[0055] 65 g of epoxy resin EPON SU8, 30 g of active ester curing agent EPI CLON HPC-800-65T, 0.3 g of dimethylaminoethanol, 4 g of cellulose nano whiskers, 5 g of high temperature resistant additives, and 4 g of diphenyl iodonium hexafluorophosphate were added to 90 g of diethylene glycol methyl ethyl ether, and the components were stirred and mixed to obtain a photoresist.
[0056] Comparative Example 4
[0057] Photoresist manufacturing
[0058] 65 g of epoxy resin EPON SU8, 30 g of active ester curing agent EPI CLON HPC-800-65T, 0.3 g of dimethylaminoethanol, 4 g of composite toughening filler, 5 g of ternary chloroacetic acid resin, and 4 g of diphenyliodonium hexafluorophosphate were added to 90 g of diethylene glycol methyl ethyl ether, and the components were stirred and mixed to obtain a photoresist.
[0059] Performance Testing
[0060] The photoresists manufactured in Examples 1 to 4 and Comparative Examples 1 to 4 were spin-coated on blank glass, respectively, and the rotation speed was controlled to adjust the thickness of the photoresist to 1 μm, and then dried at 200°C. The manufactured photoresists were placed in a constant temperature box, and the deformation time of the photoresists was tested in a 250°C environment to determine the high temperature resistance of the photoresists; the photoresists were subjected to a 180° peel strength test in accordance with GB / T 2792-2014 standard to determine the viscosity of the photoresists; photoresist films meeting the test specifications were prepared, and the elongation at break test of the photoresist films was performed in accordance with GB / T 30776-2014, and the test results are shown in the following table:
[0061] Deformation time / h Peel strength / N / 25mm Elongation at break / % Example 1 24 14.9 243 Example 2 28 16.2 251 Example 3 26 15.8 248 Example 4 25 15.3 246 Comparative Example 1 12 9.4 234 Comparative Example 2 18 13.4 152 Comparative Example 3 21 14.1 198 Comparative Example 4 15 12.6 238
[0062] As can be seen from the above table, the photoresists manufactured by Examples 1 to 4 of the present invention have excellent high temperature resistance, viscosity and toughness. Comparative Example 1 does not add high temperature resistant additives, and cannot utilize the rigid high temperature resistant benzene rings and high bond energy silicon oxygen bonds introduced into the ternary chloroacetic acid resin, and can be entangled with the epoxy resin matrix to enhance the high temperature resistance and viscosity. Therefore, the peel strength test and high temperature resistance test results are poor. Comparative Example 2 does not add composite toughening fillers, and cannot utilize cellulose nano whiskers to enhance the toughness of the epoxy resin matrix, and the gelatin grafted cellulose nano whiskers are entangled with the epoxy resin matrix. knot, improving toughness and viscosity, so the elongation at break test and peel strength test results are poor; Comparative Example 3 adds cellulose nano whiskers, which has the effect of enhancing toughness, but the cellulose nano whiskers are directly added without modification, have poor compatibility with the epoxy resin matrix, are prone to agglomeration, and cannot be entangled with the matrix, which is insufficient to enhance viscosity, so the elongation at break test and peel strength test results are poor; Comparative Example 4 adds ternary chloroacetic acid resin, but the improvement in viscosity and high temperature resistance is small, so the peel strength test and high temperature resistance test results are poor.
[0063] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A photoresist specially used for high-precision radio frequency antenna, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of epoxy resin, 25-45 parts of active ester curing agent, 0.1-0.5 parts of curing accelerator, 3-5 parts of composite toughening filler, 4-6 parts of high temperature resistant additive, 3-6 parts of photoacid generator, and 80-100 parts of solvent; The preparation method of the composite toughening filler comprises the following steps: Step A, adding cellulose nano whiskers to dimethyl sulfoxide, stirring and mixing evenly, introducing nitrogen protection, adding p-formylbenzoic acid and p-toluenesulfonic acid, then raising the temperature to 90-100° C., stirring and reacting for 4-6 hours, filtering, washing, and drying to obtain modified cellulose nano whiskers; Step B, dispersing the modified cellulose nano whiskers in deionized water to form a uniform dispersion, introducing nitrogen protection, adding gelatin, adjusting the pH, stirring and reacting at 50-60° C. for 3-6 hours, centrifugally separating, washing, and drying to obtain a composite toughening filler; The preparation method of the high temperature resistant additive is as follows: Add 1,4-phenylenedi(dimethylsilanol) to dimethyl sulfoxide, introduce nitrogen protection, stir for 10-15 minutes, add ternary chloroacetic acid resin and acid binding agent, raise the temperature to 70-90°C, react for 5-8 hours, and after the reaction is completed, cool to room temperature, precipitate, filter, wash, and vacuum dry at 40-60°C to obtain a high temperature resistant additive.
2. The photoresist for high-precision radio frequency antenna according to claim 1, characterized in that: In step B, the pH is 4.5-5.
5.
3. The photoresist for high-precision radio frequency antenna according to claim 1, characterized in that: The acid binding agent is sodium carbonate or sodium bicarbonate.
4. The photoresist for high-precision radio frequency antenna according to claim 1, characterized in that: The epoxy resin is EPON SU8; the active ester curing agent is EPICLON HPC-8000-65T; the curing accelerator is dimethylaminoethanol; the photoacid generator is any one of diphenyliodonium hexafluorophosphate, diphenyl p-tert-butylphenyl trifluoromethanesulfonate, and diphenyl p-isobutylphenyl trifluoromethanesulfonate.
5. The photoresist dedicated to high-precision radio frequency antenna according to claim 1, characterized in that: The solvent is any one of ethylene glycol monomethyl ether acetate, propylene glycol methyl ether, diethylene glycol dimethyl ether, propylene glycol methyl ether acetate, diethylene glycol methyl ethyl ether, methyl ethyl ketone, isopropyl alcohol, and cyclohexanone.
6. A method for manufacturing a photoresist dedicated to a high-precision radio frequency antenna as claimed in claim 1, characterized in that: As shown below: According to parts by weight, epoxy resin, active ester curing agent, curing accelerator, composite toughening filler, high temperature resistant additive and photoacid generator are added into the solvent, and the components are stirred and mixed evenly to obtain the photoresist.
Citation Information
Patent Citations
A photoresist composition
CN110441989B
Ultraviolet curing epoxy adhesive as well as preparation method and application thereof
CN112680159A